Pelatihan Membuat Slide Presentasi Berbasis AI Menggunakan Tome.app Kepada Siswa SMKN 1 Pangkalan Kuras - Roki Hardianto; Wirdahchoiriah; Muammar Revnu Ohara (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2023)
The rapid development of AI can help users in completing their tasks. As a teacher, administrative tasks are one of the burdens that must be completed to support the learning process. By using AI, this task can be completed more quickly. This is supported by the existence of a platform that helps in doing tasks that are usually done independently. SMKN 1 Pangkalan Kuras currently lacks educators and education personnel who are qualified in the field of information technology, this will certainly cause SMK graduates who can work to become the demands of the world of work. Because SMK is based on producing graduates who have competence in their fields. With this condition, it is necessary to conduct training activities and workshops to increase knowledge in the field of information technology to educators. Lecturers of the Faculty of Computer Science of Lancang Kuning University provided this training to educators of SMKN 1 Pangkalan Kuras to overcome problems in students. The implementation was carried out using lecture, practice and discussion methods in the computer laboratory. This activity will produce scientific journals, news of activities published in the mass media and draft teaching modules that can be useful for participants.